Functioning and neurocognition in very early and early-life onset bipolar disorders: the moderating role of bipolar disorder type. - Sleurs, D.; Speranza, M.; Etain, B.; Aouizerate, B.; Aubin, V.; Bellivier, F.; Belzeaux, R.; Carminati, M.; Courtet, P.; Dubertret, C.; Fredembach, B.; Haffen, E.; et al. (European Child & Adolescent Psychiatry, 2024)
Defining homogeneous subgroups of bipolar disorder (BD) is a major goal in personalized psychiatry and research. According to the neurodevelopmental theory, age at onset may be a key variable. As potential trait markers of neurodevelopment, cognitive and functional impairment should be greater in the early form of the disease, particularly type 1 BD (BD I). The age at onset was assessed in a multicenter, observational sample of 4190 outpatients with BD. We used a battery of neuropsychological tests to assess six domains of cognition. Functioning was measured using the Functioning Assessment Short Test (FAST). We studied the potential moderation of the type of BD on the associations between the age at onset and cognitive and functioning in a subsample of 2072 euthymic participants, controlling for potential clinical and socio-demographic covariates. Multivariable analyses showed cognition to not be impaired in individuals with early (21–30 years) and very early-life (before 14 years) onset of BD. Functioning was equivalent between individuals with early and midlife-onset of BD II and NOS but better for individuals with early onset of BD I. In contrast, functioning was not worse in individuals with very early-onset BD I but worse in those with very early-onset BD II and NOS. Early-life onset BDs were not characterized by poorer cognition and functioning. Our results do not support the neurodevelopmental view that a worse cognitive prognosis characterizes early-life onset BD. This study suggests that functional remediation may be prioritized for individuals with midlife-onset BD I and very early life onset BD 2 and NOS.